Techno-economic and consumer-economic paradigms and their compliance - Zianchuk, Mikalai F. (Journal of the Belarusian State University. Economics, 2023)
In the modern theory of innovative development, the concept of techno-economic paradigm occupies a significant place. At the same time, in published research papers on this topic the role of consumer innovations has not been studied separately from industrial innovations. However, innovative consumer goods and the consumer-economic paradigms they form play an independent role in economic growth. A specific techno-economic paradigm and the consumer-economic paradigm generated by it are not an inseparable whole and may not coincide both in time and geographically, by country. The difference in the impact of industrial and consumer innovations on economic growth is revealed. Such a phenomenon as consumer-economic paradigm is considered. The circumstances and consequences for the national economy are analysed from advancing and lagging the consumer-economic paradigm from the corresponding techno-economic paradigm.